Pengelolaan Menuju Partisipasi: Strategi Guru dalam Menumbuhkan Semangat Belajar Matematika (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Mathematics learning demands optimal student activity, concentration, and participation. However, many students still exhibit a passive attitude during the learning process, resulting in learning outcomes that have not reached the expected level. This article aims to analyze various effective classroom management strategies for fostering enthusiasm for learning and increasing student participation in mathematics learning. This study uses a library research method by reviewing various scientific sources, such as journals, academic books, and relevant research reports. The results of the study indicate that effective classroom management plays a crucial role in creating a conducive, interactive, and student-centered learning environment. Teachers function not only as transmitters of material but also as facilitators and administrators capable of building positive social relationships and motivating students to actively think and participate. Preventive, curative, and repressive classroom management strategies have been proven to improve student focus, motivation, and learning outcomes, especially when integrated with learning approaches such as discovery learning, teacher-centered learning, and the use of creative methods like squad games and block systems. Thus, adaptive and innovative classroom management is key to realizing participatory, enjoyable, and meaningful mathematics learning for the development of students' overall potential.